Comprehensive functional verification : the complete industry cycle - Wile, Bruce, ....-; Goss, John C., ....-; Roesner, Wolfgang, ....- (Amsterdam : Elsevier, 2005)
One of the biggest challenges in chip and system design is determining whether the hardware works correctly. That is the job of functional verification engineers and they are the audience for this comprehensive text from three top industry professionals. As designs increase in complexity, so has the value of verification engineers within the hardware design team. In fact, the need for skilled verification engineers has grown dramatically-functional verification now consumes between 40 and 70 per cent of a project's labor, and about half its cost. Currently there are very few books on verification for engineers, and none that cover the subject as comprehensively as this text. A key strength of this book is that it describes the entire verification cycle and details each stage. The organization of the book follows the cycle, demonstrating how functional verification engages all aspects of the overall design effort and how individual cycle stages relate to the larger design process. Throughout the text, the authors leverage their 35 plus years experience in functional verification, providing examples and case studies, and focusing on the skills, methods, and tools needed to complete each verification task. Additionally, the major vendors (Mentor Graphics, Cadence Design Systems, Verisity, and Synopsys) have implemented key examples from the text and made these available on line, so that the reader can test out the methods described in the text. This book provides comprehensive overview of the complete verification cycle. It combines industry experience with a strong emphasis on functional verification fundamentals and includes industry examples and real-world case studies.
Keywords: Computer engineering; Geïntegreerde schakelingen; Integrated circuits -- Verification; Logische schakelingen